Preparation method of high-polarization bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic

By controlling the chemical composition and annealing treatment of iron-titanium-titanic acid-titanic acid pyrine-titanic iliac-based iron and electric ceramic ceramics, the problem of defects caused by the volatilization of lead and the volatilization of the pupae, which significantly improves the performance and process of ceramic voltage and iron electrical electrical electricity. Repeatability.

CN119371198AActive Publication Date: 2025-01-28CENT SOUTH UNIV

Patent Information

Application Number
CN202411949011.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-01-28
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

During the preparation process, existing bismuth ferrate-lead titanate-barium zirconate ferroelectric ceramics have defects due to the volatility of lead and bismuth elements, which affects the piezoelectric activity and electrohysteresis loop performance of the ceramics.

Method used

By controlling the proportion of PT's Moore to 0.25, the Moore score of BF and BZT is adjusted, so that the system is near the quasi -similar phase -shaped phase of the three -party phase and the four parties, and annealing treatment is 450 ~ 650 ° C, the time is 10 ~ 120 minutes to reduce defects and improve ceramic performance.

Benefits of technology

A significant reduction of the volatilization of lead, reducing the production of defects, improving the performance of ceramics for piezoelectric and iron electrical, the saturated polarization intensity increased by more than 100%, D33 increased by more than 7 times, which improved the repeatability and quality control of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371198A_ABST
    Figure CN119371198A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of high-polarization bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic, which comprises the following steps: preparing oxide raw materials according to the chemical formula of the bismuth ferrite-barium titanate ceramic-based ferroelectric ceramic, mixing to obtain mixed powder, pre-sintering the mixed powder to obtain pre-sintered powder, granulating the pre-sintered powder to obtain granules, and sintering the granules to obtain the high-polarization bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic. Performing compression molding on the granules to obtain a green body, performing degumming sintering on the green body to obtain sintered ceramic, and performing annealing treatment on the sintered ceramic to obtain the bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic. According to the invention, annealing treatment is carried out on sintered ceramic, after annealing treatment, defect dipoles generated by volatilization of Pb and Bi in the ceramic are rearranged under the action of a temperature field, relaxor ferroelectric-ferroelectric phase change occurs in a ceramic phase, a ferroelectric hysteresis loop reflects that the girdling of the loop is opened, and the rectangularity is increased; a bipolar strain curve is converted into a typical butterfly shape of ferroelectric from a bud shape, and the ferroelectricity of the ceramic is further greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-temperature piezoelectric ceramics, and in particular relates to a method for preparing a bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic with high polarization strength. Background Art

[0002] With the development of industrial automation and aerospace technology, high-temperature piezoelectric ceramics are widely used in high-temperature sensors, actuators and ultrasonic equipment. The development and optimization of piezoelectric ceramics with high Curie temperature, high performance and excellent temperature stability have become key research issues. Bismuth ferrite (BiFeO3, BFO) has a high Curie temperature (~825 ℃) and a large polarization strength, but due to its poor piezoelectric activity, it is often dissolved with other high-voltage electrically active perovskite ferroelectric ceramics to obtain a multi-component bismuth ferrite-based ceramic system with both high Curie temperature and high piezoelectricity. Among them, bismuth ferrite-lead titanate-barium zirconate titanate (BiFeO3-PbTiO3-Ba(Zr,Ti)O3, BF-PT-BZT) based ferroelectric ceramics have attracted much attention due to their high Curie temperature, high polarization strength and good piezoelectric properties. However, during the preparation process, due to the volatility of lead and bismuth elements, Fe 2+ / Fe 4+ Defects such as ions and oxygen vacancies are easy to form, resulting in large leakage current and dielectric loss, and the hysteresis loop is not easy to open, thus limiting its performance.

[0003] According to the existing technical means, the optimization treatment of BF-PT-BZT has only been reported on the regulation of the MPB phase boundary components, that is, by changing the content of BF, PT, and BZT components, the ceramic system is in a state of multi-phase coexistence at room temperature, reducing the energy barrier of domain reversal, thereby improving the piezoelectric activity of the ceramic. The saturated polarization strength of the ceramic prepared by this method can reach 10-47 μC / cm 2 However, due to the fluctuation of the thermal field during the sintering process, the volatilization of lead and bismuth elements cannot be avoided. The influence of lead vacancies has a great influence on the performance of ceramics. The generation of defects will cause pinning of domain walls, resulting in a narrow waist of the hysteresis loop. The piezoelectric and ferroelectric activity of ceramics cannot be fully stimulated, and the process repeatability is poor. In addition, the above method requires the addition of a higher content of PT, and the excessive volatilization of lead is not friendly to the environment. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramics with high polarization strength. The preparation method of the present invention is simple and controllable, can greatly reduce the volatilization of lead, and is more environmentally friendly.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The invention discloses a method for preparing a bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic with high polarization strength. The method comprises the following steps: according to the chemical formula of the bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic, various oxide raw materials are mixed to obtain a mixed powder, the mixed powder is pre-fired to obtain a pre-fired powder, the pre-fired powder is granulated to obtain a pellet, the pellet is pressed to obtain a green body, the green body is subjected to binder removal and sintering to obtain a sintered ceramic, and the sintered ceramic is subjected to annealing to obtain the bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic.

[0007] The annealing temperature is 450-650°C and the annealing time is 10-120 min;

[0008] The chemical formula of the bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic is: 0.56BiFeO3-0.25Pb (1+x) TiO3-0.19Ba(Zr 0.25 Ti 0.75 )O3, where x is 0~0.05.

[0009] The present invention provides a method for preparing a bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic with high polarization strength. On the one hand, the present invention controls the molar ratio of PT in the bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic to a lower 0.25, reduces the total content of Pb, and then adjusts the molar fractions of the two end members BF and BZT to obtain 0.56BF-0.25PT-0.19BZT. At this time, the system is near the quasi-modular phase boundary (MPB) where the rhombohedral phase and the tetragonal phase coexist. The energy barrier required for domain reversal is low, and the piezoelectric activity is high. Combined with the excess of the Pb element in the chemical formula, the applicant has found that it can effectively inhibit the volatilization of lead and thus inhibit the generation of vacancies. , reducing the generation of defects, weakening the pinning effect of defects on domains, and reducing the waist phenomenon of the BF-PT-BZT ceramic PE curve; on the other hand, the present invention performs annealing treatment on the sintered ceramic. After annealing, the defect dipoles generated by the volatilization of Pb and Bi inside the ceramic are rearranged under the action of the temperature field, and a relaxation ferroelectric-ferroelectric phase transition occurs in the ceramic phase, which is reflected in the hysteresis loop as the waist of the loop opens and the rectangularity increases, and the bipolar strain curve changes from a bud type to a typical butterfly type of ferroelectrics, and the ferroelectricity of the ceramic is further greatly improved.

[0010] The preferred solution is to prepare Fe2O3, PbO, TiO2, BaCO3, and ZrO2 according to the stoichiometric ratio of the bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic chemical formula, and prepare Bi2O3 according to an excess of 1 mol% of the Bi element. When preparing the bismuth ferrite-barium titanate ceramic-based ferroelectric ceramic, the Bi element is appropriately excessive to compensate for the volatilization of the bismuth element so that the final product conforms to the chemical formula. Although the volatilization of the bismuth element is compensated by the ingredients, the volatilization of the bismuth element cannot be avoided, and defects will still occur.

[0011] In a preferred embodiment, the mixing method is wet ball milling, the medium of the wet ball milling is anhydrous ethanol, the rotation speed of the wet ball milling is 250-400 r / min, and the wet ball milling time is 8-12 h.

[0012] Further preferably, during the wet ball milling, the grinding balls are composed of zirconium balls with diameters of 7-10 mm, 5-7 mm, and 3-5 mm in a mass ratio of 5-5.9:3-3.9:2-2.9.

[0013] More preferably, during the wet ball milling, the ball-to-material ratio is 5-10:1.

[0014] The above-mentioned ball milling parameters can fully mix and refine the raw material powders, thereby promoting a more complete subsequent reaction.

[0015] In the actual operation process, the mixture obtained after wet ball milling is dried in an oven and then sieved and pre-calcined.

[0016] In a preferred embodiment, the pre-burning temperature is 800-850° C. and the pre-burning time is 2-4 hours.

[0017] More preferably, the heating rate of the pre-calcination is 5-10°C / min.

[0018] The preferred solution is to ball-mill the calcined powder and then sieve it, add PVB as a binder and use anhydrous ethanol as a medium for granulation, then dry it at 70-80°C and grind it, and then sieve it through a 120-mesh sieve to obtain the granules, in which the mass fraction of PVB is 1-3%.

[0019] Preferably, the pressing pressure is 1.2-1.5 MPa, and the holding time is 30-60 s.

[0020] By controlling the pressing pressure within the above range, there are fewer defects, higher density, and the size preparation can be guaranteed to avoid the generation of cracks. By maintaining the pressure for 30 to 60 seconds, the influence of elastic aftereffect is avoided.

[0021] The preferred solution is to place the green body in a small crucible covered with pre-burned powder, invert a large crucible outside the sealed small crucible, and use a double crucible method to perform debinding sintering. In the present invention, by placing the green body in a small crucible covered with pre-burned powder, the double crucible method can reduce the volatilization of elements.

[0022] In a preferred embodiment, the green body is subjected to binder removal and sintering as follows: firstly, the temperature is raised to 500-600°C at a heating rate of 1-3°C / min and kept at that temperature for 2-4 hours for binder removal, and then the temperature is raised to 1000-1100°C at a heating rate of 5-10°C / min and kept at that temperature for 2-4 hours for sintering. After sintering, the green body is cooled in the furnace.

[0023] In the present invention, the binder is first debonded at a slower heating rate, so that the binder can be fully decomposed and removed and the ceramic sheet can be prevented from cracking. After the binder is debonded, a faster heating rate is directly used to sinter at the sintering temperature to reduce the volatilization of Pb and Bi. Of course, the heating rate during sintering cannot be too fast. If it is too fast, it will not be conducive to the discharge of internal pores, which will affect the densification process, increase the introduction of defects, and cause grain refinement. Too small grain size will cause the deterioration of piezoelectric performance to a certain extent, while too slow will lead to too long sintering time, increased volatilization of Pb and Bi, and increased concentration of defects inside the material, thereby causing deterioration of electrical performance.

[0024] Preferably, the annealing process is: firstly heating to 600-650°C at a heating rate of 5-10°C / min, keeping warm for 10-20 min, then cooling to 450-550°C at a cooling rate of 5-10°C / min, keeping warm for 100-120 min, and cooling with the furnace.

[0025] The applicant has found that the annealing procedure has a great influence on the final performance. According to the above-mentioned procedure of the present invention, the temperature is first appropriately increased and then cooled to 450-550°C for sufficient heat preservation, which can ensure that the defects in the system have enough time to be fully arranged, and the performance of the final piezoelectric ceramic is optimal.

[0026] In a preferred embodiment, the chemical formula of the bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic is: 0.56BiFeO3-0.25Pb (1+x) TiO3-0.19Ba(Zr 0.25 Ti 0.75 )O3, where x is 0.02~0.04.

[0027] In the present invention, the defects can be effectively reduced by reducing the PT content and appropriately increasing the Pb content. However, if the Pb content is too high, defects will be reintroduced, resulting in enhanced diffusion of the ferroelectric ceramic, a tendency for the hysteresis loop to reappear with a waist, and deterioration of electrical properties.

[0028] Beneficial Effects

[0029] The preparation method of the present invention can rearrange defects in ceramics and increase domain conversion switches, reduce the negative impact of defects, improve process repeatability, improve quality control, and greatly enhance the piezoelectric and ferroelectric properties of ceramics. The polarization intensity of the heat-treated samples is increased by more than 100% compared with the previous ones. 33 It has increased by more than 7 times, optimized the yield and quality of BF-PT-BZT ceramics, improved production efficiency, and provided technical support for the mass production and application of functional ceramics in this system. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Actual picture of the bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic prepared in Example 1.

[0031] Figure 2 The actual picture of the bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic prepared in Example 1 after silver batching.

[0032] Figure 3 The program curve of annealing treatment in Example 1.

[0033] Figure 4 The SEM image of the sintered ceramic provided in the embodiment, wherein: Figure 4 (a) is the cross-sectional SEM image of the sintered ceramic when x=0.00. Figure 4 (b) is the cross-sectional SEM image of the sintered ceramic when x=0.01. Figure 4 (c) is the cross-sectional SEM image of the sintered ceramic when x=0.02. Figure 4 (d) is the cross-sectional SEM image of the sintered ceramic when x=0.03. Figure 4 (e) is the cross-sectional SEM image of the sintered ceramic when x=0.04. Figure 4 (f) is the cross-sectional SEM image of the sintered ceramic when x=0.05.

[0034] Figure 5 (a) PE curve and (b) SE curve of ceramic when x=0.00.

[0035] Figure 6 (a) PE curve and (b) SE curve of ceramic when x=0.02.

[0036] Figure 7 (a) PE curve and (b) SE curve of ceramic when x=0.04.

[0037] Figure 8 is the cross-sectional morphology before and after annealing when x=0.00, where Figure 8 (a) before annealing, Figure 8 (b) After annealing. DETAILED DESCRIPTION

[0038] Example 1

[0039] Step 1. According to 0.56BiFeO3-0.25Pb (1+x) TiO3-0.19Ba(Zr 0.25 Ti 0.75)O3 ferroelectric ceramic chemical formula, x is 0.00, the corresponding raw materials Bi2O3, Fe2O3, PbO, TiO2, BaCO3, ZrO2 are weighed according to the stoichiometric ratio; among which Bi element is added according to Bi 1.01 FeO3 is 1 mol% excess to prepare Bi2O3;

[0040] Step 2. Place the raw material powder and zirconium balls with particle sizes of 7 mm, 5 mm, and 3 mm in a ball mill at a mass ratio of 5:3:2, add an appropriate amount of alcohol, seal the ball mill, and ball mill at a speed of 250 r / min for 8 hours;

[0041] Step 3. The ball-milled powder is placed in a 75°C oven for drying, sieved, and pre-calcined at a temperature of 800-850°C;

[0042] Step 4. The pre-sintered powder is subjected to secondary ball milling at a speed of 400 r / min for 10 h;

[0043] Step 5. Dry the powder after the second ball milling, sieve it, add an appropriate amount of PVB binder, dissolve it in alcohol to granulate it, and dry it in a 75°C oven;

[0044] Step 6. Place the dried granulated powder in a mortar, grind and sieve it through a 120-mesh sieve;

[0045] Step 7. Place the ceramic powder obtained in step 6 in a mold with a diameter of 10 mm, apply a pressure of 1.2-1.5 MPa, maintain the pressure for 30 s, and press into a cylindrical green body;

[0046] Step 8. Place the green body in a small crucible covered with sintering powder, invert the large crucible outside the sealed small crucible, and use the double crucible method to debind and sinter; the high-temperature sintering furnace is heated to 550 °C at 3 °C / min and kept warm for 240 min, then heated to 1020 °C at 5 °C / min and kept warm for 120 min, and finally cooled to room temperature with the furnace to obtain a sintered body.

[0047] Step 9: Place the sintered sample in an annealing furnace for annealing. The specific annealing procedure (such as Figure 3 The temperature was first raised to 600 °C at 5 °C / min, kept at that temperature for 10 min, then dropped to 500 °C at 10 °C / min, kept at that temperature for 120 min, and then cooled with the furnace.

[0048] Step 10. When the sample cools to room temperature, take out the sample to obtain bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramics.

[0049] Example 2

[0050] Step 1. According to 0.56BiFeO3-0.25Pb(1+x) TiO3-0.19Ba(Zr 0.25 Ti 0.75 )O3 ferroelectric ceramic chemical formula, x is 0.02, the corresponding raw materials Bi2O3, Fe2O3, PbO, TiO2, BaCO3, ZrO2 are weighed according to the stoichiometric ratio; among which Bi element is added according to Bi 1.01 FeO3 is 1 mol% excess to prepare Bi2O3;

[0051] Step 2. Place the raw material powder and zirconium balls with a particle size composition of 5:3:2 in a ball mill, add an appropriate amount of alcohol, seal the ball mill, and mill at a speed of 250 r / min for 8 h;

[0052] Step 3. The ball-milled powder is placed in a 75°C oven for drying, sieved, and pre-calcined at a temperature of 800-850°C;

[0053] Step 4. The pre-sintered powder is subjected to secondary ball milling at a speed of 400 r / min for 10 h;

[0054] Step 5. Dry the powder after the second ball milling, sieve it, add an appropriate amount of PVB binder, dissolve it in alcohol to granulate it, and dry it in a 75°C oven;

[0055] Step 6. Place the dried granulated powder in a mortar, grind and sieve it through a 120-mesh sieve;

[0056] Step 7. Place the ceramic powder obtained in step 6 in a mold with a diameter of 10 mm, apply a pressure of 1.2-1.5 MPa, maintain the pressure for 30 s, and press into a cylindrical green body;

[0057] Step 8. Place the green body in a small crucible covered with sintering powder, invert the large crucible outside the sealed small crucible, and use the double crucible method to debind and sinter; the high-temperature sintering furnace is heated to 550 °C at 3 °C / min and kept warm for 240 min, then heated to 1040 °C at 5 °C / min and kept warm for 120 min, and finally cooled to room temperature with the furnace to obtain a sintered body.

[0058] Step 9: Place the sintered sample in an annealing furnace for annealing. The specific annealing procedure is as follows:

[0059] First, heat up to 600 °C at 5 °C / min, keep warm for 10 min, then decrease to 510 °C at 10 °C / min, keep warm for 120 min, and cool with the furnace.

[0060] Step 10. When the sample cools to room temperature, take out the sample to obtain bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramics.

[0061] Example 3

[0062] Step 1. According to 0.56BiFeO3-0.25Pb (1+x) TiO3-0.19Ba(Zr 0.25 Ti 0.75 )O3 ferroelectric ceramic chemical formula, x is 0.04, the corresponding raw materials Bi2O3, Fe2O3, PbO, TiO2, BaCO3, ZrO2 are weighed according to the stoichiometric ratio; among which Bi element is added according to Bi 1.01 FeO3 is 1 mol% excess to prepare Bi2O3;

[0063] Step 2. Place the raw material powder and zirconium balls with a particle size composition of 5:3:2 in a ball mill, add an appropriate amount of alcohol, seal the ball mill, and mill at a speed of 250 r / min for 8 h;

[0064] Step 3. The ball-milled powder is placed in a 75°C oven for drying, sieved, and pre-calcined at a temperature of 800-850°C;

[0065] Step 4. The pre-sintered powder is subjected to secondary ball milling at a speed of 400 r / min for 10 h;

[0066] Step 5. Dry the powder after the second ball milling, sieve it, add an appropriate amount of PVB binder, dissolve it in alcohol to granulate it, and dry it in a 75°C oven;

[0067] Step 6. Place the dried granulated powder in a mortar, grind and sieve it through a 120-mesh sieve;

[0068] Step 7. Place the ceramic powder obtained in step 6 in a mold with a diameter of 10 mm, apply a pressure of 1.2-1.5 MPa, maintain the pressure for 30 s, and press into a cylindrical green body;

[0069] Step 8. Place the green body in a small crucible covered with sintering powder, invert the large crucible outside the sealed small crucible, and use the double crucible method to debind and sinter; increase the temperature in the high-temperature sintering furnace to 550 °C at 3 °C / min and keep it for 240 min, then increase the temperature to 1060 °C at 5 °C / min and keep it for 120 min, and finally cool it to room temperature with the furnace to obtain a sintered body.

[0070] Step 9: Place the sintered sample in an annealing furnace for annealing. The specific annealing procedure is as follows:

[0071] First, heat up to 600 °C at 5 °C / min, keep warm for 10 min, then decrease to 520 °C at 10 °C / min, keep warm for 120 min, and cool with the furnace.

[0072] Step 10. When the sample cools to room temperature, take out the sample to obtain bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramics.

[0073] Example 4

[0074] In addition to the above examples, in order to better compare the values ​​of x, sintered green bodies with x values ​​of 0.01, 0.03, and 0.05 were prepared in the manner of Example 1.

[0075] Example 5

[0076] The other conditions were the same as those in Example 1, except that the specific annealing procedure was as follows: first, the temperature was raised to 600°C at a heating rate of 5°C / min and kept at that temperature for 10 min.

[0077] Performance Testing

[0078] The cross section of the sintered green body with x=0-0.05 was characterized using a MIRA4 LMH scanning electron microscope produced by Czech TESCAN Company. Figure 4 As shown in the figure, by adjusting the x content, the fracture mode of the ceramic changes from transgranular fracture to intergranular fracture, which means that when the lead content is low, there are more defects inside the ceramic, and the increase of x content can reduce the defect concentration, thereby improving the ceramic performance and density. The sample was then annealed and the cross section of the sintered blank after annealing was characterized, as shown in Figure 2. Figure 8 As shown in the figure, the samples that were mainly transgranular fractured before heat treatment mostly showed intergranular fracture after heat treatment, which indicates that under the action of the temperature field, the defects were rearranged and the grain strength was enhanced.

[0079] The sintered green body obtained in the above embodiment and the bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic obtained after annealing were polished and then coated with silver.

[0080] The dynamic hysteresis loop test of the BF-PT-0.19BZT ferroelectric ceramics in Examples 1, 2, 3, 4, and 5 was performed using the ferroelectric analyzer Agilent TF2000. It was found that the saturation enhancement strength Pr of the samples before heat treatment independently measured under the Sawyer-Towers bridge was 3.18 μC / cm 2 (x=0.00), 7.53 μC / cm 2 (x=0.01), 14.96 μC / cm 2 (x=0.02), 15.67 μC / cm 2 (x=0.03), 19.33 μC / cm 2 (x=0.04), 17.02 μC / cm 2(x=0.05) By adjusting the content of x, the optimal ferroelectric component was obtained at x=0.04, the residual polarization value increased by more than 5 times, and the SE curve changed from a bud type to a standard butterfly curve, and the negative strain increased from 0% at x=0 to 0.04% at x=0.04. This shows that the increase in Pb content can effectively reduce the waist phenomenon caused by defect pinning, which is conducive to the full stimulation of polarization potential. However, if the Pb content is too high, defects will be reintroduced and the performance will be reduced. The heat treatment results show that the defect dipoles generated by the volatilization of Pb and Bi inside the ceramic are rearranged under the action of the temperature field, and a relaxed ferroelectric-ferroelectric phase transition occurs in the ceramic phase, which is reflected by the hysteresis loop as the waist of the loop opens and the rectangularity increases. The bipolar strain curve changes from a bud type to a typical butterfly type of ferroelectrics (Example 1, Example 2), and its residual polarization value is increased to 32.23 μC / cm 2 (x=0.00), 35.65 μC / cm 2 (x=0.02), which are 9 times and 1.4 times higher than those before heat treatment, and the saturation polarization value is also increased from ~20 μC / cm 2 Improved to ~40 μC / cm 2 At the same time, for the sample with good ferroelectricity before heat treatment (Example 3), its ferroelectricity is still improved after heat treatment, Pr is increased by 15%, and the hysteresis loop is as follows Figure 5 , 6 In addition, the heat treatment procedure has a great influence on the performance improvement. The P measured in Example 5 r =23 μC / cm 2 , which is 72% of that in Example 1.

[0081] The samples were subjected to oil bath polarization for 20 min at 100 °C and 5 kV / mm using the MPD PLUS oil bath high voltage polarization device. 33 The piezoelectric coefficient was measured by a measuring instrument. Before heat treatment, the d 33 They are 33 pC / N, 185 pC / N, 240 pC / N, and the d 33 They were 265 pC / N, 272 pC / N, and 290 pC / N, which were higher than those before heat treatment. 33 The increase was 20%-700%, while in Example 5, d 33 =200 pC / N, which is 75% of that in Example 1.

Claims

1. A method for preparing a bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic with high polarization strength, characterized in that: According to the chemical formula of bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramic, various oxide raw materials are mixed to obtain mixed powder, the mixed powder is pre-sintered to obtain pre-sintered powder, the pre-sintered powder is granulated to obtain pellets, the pellets are pressed to obtain green bodies, the green bodies are debinded and sintered to obtain sintered ceramics, and the sintered ceramics are annealed to obtain bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramics; The annealing temperature is 450-650°C and the annealing time is 10-120 min; The chemical formula of the bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic is: 0.56BiFeO3-0.25Pb (1+x) TiO3-0.19Ba(Zr 0.25 Ti 0.75 )O3, where x is 0~0.

05.

2. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 1, characterized in that: Fe2O3, PbO, TiO2, BaCO3, and ZrO2 are prepared in a stoichiometric ratio according to the chemical formula of bismuth ferrite-lead titanate-barium zirconate titanate-based ferroelectric ceramics, and Bi2O3 is prepared in an excess of 1 mol% of Bi element.

3. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 1, characterized in that: The mixing method is wet ball milling, the medium of the wet ball milling is anhydrous ethanol, the speed of the wet ball milling is 250-400 r / min, and the time of the wet ball milling is 8-12 h; During the wet ball milling, the grinding balls are composed of zirconium balls with diameters of 7-10 mm, 5-7 mm, and 3-5 mm in a mass ratio of 5-5.9:3-3.9:2-2.9; During the wet ball milling, the ball-to-material ratio is 5-10:

1.

4. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 3, characterized in that: The pre-burning temperature is 800-850°C and the pre-burning time is 2-4h; The heating rate of the pre-calcination is 5-10°C / min.

5. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 3, characterized in that: The calcined powder is ball-milled and sieved, PVB is added as a binder and granulated with anhydrous ethanol as a medium, and then dried at 70-80°C and ground, and then sieved through a 120-mesh sieve to obtain granules, in which the mass fraction of PVB is 1-3%.

6. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 3, characterized in that: The pressing pressure is 1.2-1.5 MPa, and the holding time is 30-60 s.

7. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 1, characterized in that: The green body is placed in a small crucible covered with pre-burned powder, a large crucible is placed inverted outside the sealed small crucible, and debinding and sintering are performed using a double crucible method.

8. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 1 or 7, characterized in that: The process of debinding and sintering the green body is as follows: firstly, heating the temperature to 500-600°C at a heating rate of 1-3°C / min and keeping the temperature for 2-4 hours for debinding, and then heating the temperature to 1000-1100°C at a heating rate of 5-10°C / min and keeping the temperature for 2-4 hours for sintering.

9. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 1, characterized in that: The annealing process is as follows: firstly, heating to 600-650°C at a heating rate of 5-10°C / min, keeping the temperature for 10-20 min, then cooling to 450-550°C at a cooling rate of 5-10°C / min, keeping the temperature for 100-120 min, and cooling with the furnace.

10. The method for preparing a high polarization strength bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic according to claim 1, characterized in that: The chemical formula of the bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic is: 0.56BiFeO3-0.25Pb (1+x) TiO3-0.19Ba(Zr 0.25 Ti 0.75 )O3, where x is 0.02~0.04.

Citation Information

Patent Citations

  • Preparation method for bismuth ferrite-lead titanate / FTO conducting glass-structure material

    CN102863209A

  • Piezoelectric ceramic composition and piezoelectric resonator

    JP2002193664A

  • Niobium-based lead-free piezoelectric ceramic and producing method thereof

    JP2021001098A

  • High Curie temperature ternary piezoelectric ceramics

    US20120145943A1

Cited By

  • Method for enhancing pyroelectric property of ferroelectric single crystal

    CN120401019A

  • High-temperature lead-free piezoelectric ceramic material, preparation method thereof and piezoelectric ceramic device

    CN121285248A

  • A high-temperature lead-free piezoelectric ceramic material, a preparation method thereof and a piezoelectric ceramic device

    CN121285248B

  • Heat treatment method of high-polarization bismuth ferrite-lead titanate-barium zirconate titanate based ferroelectric ceramic

    CN121974676A

  • A heat treatment method of a high-polarization-strength bismuth ferrite-lead titanate-barium zirconium titanate-based ferroelectric ceramic

    CN121974676B